Piety and Property: Locke and the Development of American Protestantism - Bowden, Geoffrey C. (Christian scholar's review, 2008)
John Locke was arguably one of the most influential thinkers on American colonial political thought, but does his reach extend beyond the political realm? Geoffrey C. Bowden argues that Elisha Williams, a rector at Yale in the 1740s, appropriates Locke’s famous doctrine of property to reconceive the nature of religion as a form of personal property and resulting ecclesial institutions as based on contract. Williams’ adoption of Locke for religious thinking instantiates a form of theological discourse in America that continues on the contemporary scene. The essay concludes by querying whether religious institutions that adopt the moral and political structure of rights-based democracies can actually serve as the moral ballast to the excesses of democracy, as Tocqueville observed. Mr. Bowden is Professor of Philosophy at Malone College.